HUBUNGAN ANTARA LOGIKA PROPOSISI DENGAN LOGIKA PREDIKAT (SUATU KAJIAN EPISTEMOLOGIS) - Suyitno, Hardi (MATEMATIKA, 2006)
This paper presentsÂ epistemological studiesÂ ofÂ propositionalÂ logic andÂ predicate logic. The topic is a part of the dissertation proposal under title â€œÃ‹pistemology of Mathematical Logic According to Ludwig Wittgensteinâ€.Â Â Author is a student of the Doctor ProgramÂ of Gajah Mada University,Â the majorstudyÂ isÂ philosophy. There are someÂ difference, equality, and relation between propositionalÂ logic andÂ predicate logic.Â Both of them use the same ope-rator, method, and rule ofÂ inference. There are fiveÂ operator of logic, thatÂ areÂ disjunction, conjunction, negation, implication,Â and biimplication. The truth value of proposition deter-minated by definition.Â There are eighteen rules ofÂ inference, four rules for removing quan-tifiers,Â and four rules forÂ introducing quantifiers. There are two methods of validity test, that are direct proof and indirect proof; andÂ there is one common method for invalidity test , that is Counter Exampel Method. The basic component ofÂ propositional logic isÂ simple statement. The basic component of predicate logic is predicate. In the predicate logic beside Counter Exampel Method for invalidity test,Â there is another method for invalidity test that is Finite Universe Method.Â The conclusionÂ of this research isÂ propositional logicÂ which a part ofÂ predicate logic. IfÂ a form is valid in propositionalÂ logic, thenÂ the formÂ is valid in predicate logics. Thus scope of predicate logic is wider than propositional logic. Â